Effectiveness of various endodontic systems in treating teeth with C-shaped root canals - Irina V. Firsova; Natalia N. Trigolos; Nikolay N. Yaroshenko; Eduard S. Temkin; Maria V. Kabytova (Russian Open Medical Journal)
Introduction — C-shaped configuration is amongst the most complicated root canal varieties requiring additional effort for successful endodontic treatment. The goal of this study was the laboratory comparison of the endodontic treatment efficiencies via XP-endo vs. Gentlefile systems for the teeth with C-shaped root canals. Material and Methods — In laboratory settings, 36 teeth with established C-shaped configuration, extracted for medical reasons (24 mandibular premolars and 12 mandibular second molars), underwent the root canal treatment by XP-endo (XP) and Gentlefile (GF) systems. Treatment quality was evaluated on the basis of dye penetration tests and examination of root dentinal surface with a scanning electron microscope. The significance of differences between the groups was assessed via Mann-Whitney U test. Results — For GF instruments, the average size of stained area in the apical third of teeth was 3.33±2.73%, while in the coronal third it amounted to 13.49±13.58%. The results of using the XP instruments demonstrated the average size of stained area in the apical third equal to 15.45±12.48%, while in the coronal third it was 37.30±14.06%. The scanning electron microscopy revealed a rougher surface of dentin and the remnants of stained layer in root canals treated with GF system. Conclusion — Thus, XP instruments exhibited a better treatment quality compared with GF system. The obtained data may justify the choice of instruments for endodontic teeth treatment in case of an intricate root canal system.